Pengaruh Ruang Terhadap Psikologi Pekerja Pada Kantor M-Radio Surabaya - Wijaya, Sellin; Sari, Sriti Mayang; Pradjonggo, Celline Junica (Intra, 2019)
The mass quantity of container materials usage as an alternative to housing and offices is increasingly popular in Indonesia, especially in East Java, Surabaya. As an innovation form for a new-build office by considering the concept, construction permits, and land. The concept of the M-Radio Surabaya office was considered interesting because it carries the concept of contemporary youth. So that the concept creates an interior that uses striking colors on the walls, and the application of unique furniture. This study aims to determine the effect of psychology of workers at the M-Radio Surabaya container station that reviewed based on the aspects of Well-Designed Space according to Sally Augustin, using descriptive qualitative methods. The results shows that the M-Radio office managed to pass almost all standards and gave positive influences on its workers.